2019
DOI: 10.1002/jbm.a.36867
|View full text |Cite
|
Sign up to set email alerts
|

Strontium‐substituted biphasic calcium phosphate microspheres promoted degradation performance and enhanced bone regeneration

Abstract: Biphasic calcium phosphate (BCP) ceramics are the subject of much attention for use as bone replacement material. However, it remains a challenge to promote the degradation and osteoinductivity performances of BCP ceramics. In this work, novel BCP ceramic microspheres with good degradation and excellent osteoinductivity were prepared through high-content strontium (Sr) doping. The in vitro results indicated that the Sr10-BCP, Sr40-BCP, and Sr80-BCP microspheres all had their HA crystals partially transformed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Cells of 7–10 passages were used in the experiments. The cells were planted in 96-well plates (SPL life science, Pocheon, Korea) at a concentration of 1.5 × 10 4 cells/cm 2 , cultured for 24 h and then added to OCP and OCP-Sr at concentrations of 10.00, 3.33, 1.11, 0.37, 0.12, 0.04, and 0.01 mg/mL and were co-cultured for another 96 h. OCP and OCP-Sr samples were pre-sterilized with 75% ethanol according to the indicated method [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells of 7–10 passages were used in the experiments. The cells were planted in 96-well plates (SPL life science, Pocheon, Korea) at a concentration of 1.5 × 10 4 cells/cm 2 , cultured for 24 h and then added to OCP and OCP-Sr at concentrations of 10.00, 3.33, 1.11, 0.37, 0.12, 0.04, and 0.01 mg/mL and were co-cultured for another 96 h. OCP and OCP-Sr samples were pre-sterilized with 75% ethanol according to the indicated method [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown in Basal Medium Eagle (Sigma-Aldrich, Milwaukee, WI, USA) supplemented with heat-inactivated fetal bovine serum (Gibco, Waltham, MA, USA) to a final concentration of 10% and 2 mM L-glutamine (Sigma-Aldrich, St. Louis, MO, USA), 40 µg/mL gentamicin sulfate (Sigma-Aldrich, St. Louis, MO, USA), under conditions of 5% CO 2 content in the air and at 37 • C. Cells of 7-10 passages were used in the experiments. The cells were planted in 96-well plates (SPL life science, Pocheon, Korea) at a concentration of 1.5 × 10 4 cells/cm 2 , cultured for 24 h and then added to OCP and OCP-Sr at concentrations of 10.00, 3.33, 1.11, 0.37, 0.12, 0.04, and 0.01 mg/mL and were co-cultured for another 96 h. OCP and OCP-Sr samples were pre-sterilized with 75% ethanol according to the indicated method [48].…”
Section: Cell Culturementioning
confidence: 99%
“…For example, Chen et al. [ 165 ] reported enhanced degradation and osteoinductivity of biphasic calcium phosphate ceramic microspheres by high‐content Sr 2+ ion doping. They found that the degradation rate of materials increased with increasing doping amount of Sr 2+ ions, and 40% Sr 2+ ‐doped sample degraded more completely and significantly promoted new bone regeneration compared with HAP microspheres.…”
Section: Degradation Of Drug Nanocarriersmentioning
confidence: 99%
“…Thus, many material modification techniques have been applied to improve the physico-chemical properties of CaP ceramics in order to further enhance their bioactivity and osteogenic capacity. 3,4 In recent years, extensive studies on ion doping have been performed to introduce a variety of bioactive ions into CaP ceramics, such as magnesium (Mg), 5 zinc (Zn), 6 and strontium (Sr). 7 Among these ions, Sr has attracted great interest due to its unique chemical and biological properties.…”
Section: Introductionmentioning
confidence: 99%